How Big Tech Determines the State’s Digital Sovereignty: A Comparative Study of India and Indonesia - Kartika Putri, Dewi Anjani; Sahide, Ahmad; Rohmatika, Fiya Ainur (Jurnal Hubungan Internasional, 2026)
This comparative study examined how India and Indonesia address the dominance of Big Tech platforms under similar structural pressures, data dependency, cross-border flows, and infrastructure imbalances in their efforts to secure digital sovereignty. By applying a strategic-relational approach to analyze access to platforms, choice of instruments, and implementation patterns, as well as a structural lens of data colonialism, a qualitative comparative case study was conducted by tracking legislative processes and policy timelines (2019–2024). Empirical evidence included India's DPDP Act, IT Regulations, UPI adoption, ONDC launch, and Google's antitrust fines; as well as Indonesia's PDP Act, PP 71/2019, enforcement of PSE registration, large hyperscaler FDI commitments, and the 2023 social commerce ban, which led to the restructuring of TikTok and Tokopedia. Findings disclosed that India has enhanced its sovereignty through public infrastructure, centralized regulation, and strict enforcement, whereas Indonesia has adopted a hybrid approach, combining legal reform with dependence on foreign platforms amid fragmented institutions. Both achieved only partial sovereignty, suggesting that the selectivity of domestic institutions mediated the impact of structural constraints. Policy implications included developing digital sovereignty metrics, enhancing bureaucratic coordination, investing in indigenous infrastructure, and raising transparency in platform–government interactions.